2022
DOI: 10.3389/fnagi.2022.896522
|View full text |Cite
|
Sign up to set email alerts
|

Induction of A Disintegrin and Metalloproteinase with Thrombospondin motifs 1 by a rare variant or cognitive activities reduces hippocampal amyloid-β and consequent Alzheimer’s disease risk

Abstract: Amyloid-β (Aβ) derived from amyloid precursor protein (APP) hydrolysis is acknowledged as the predominant hallmark of Alzheimer’s disease (AD) that especially correlates to genetics and daily activities. In 2019, meta-analysis of AD has discovered five new risk loci among which A Disintegrin and Metalloproteinase with Thrombospondin motifs 1 (ADAMTS1) has been further suggested in 2021 and 2022. To verify the association, we re-sequenced ADAMTS1 of clinical AD samples and subsequently identified a novel rare v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…For example, L1CAM-FL was cleaved by ADAM10 to generate a soluble 180-kDa L1CAM (L1-180) [ 24 ]. ADAMTS1 and ADAM10 belong to the ADAM family and have both disintegrin and zinc metalloprotease domains, which implies that they might have functions related to the ECM and adhesion molecules by a similar approach [ 25 ]. Herein, we observed that overexpression and knockdown of ADAMTS1 respectively promoted and suppressed expression of L1-180 in HSC-3 and HSC-3M cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, L1CAM-FL was cleaved by ADAM10 to generate a soluble 180-kDa L1CAM (L1-180) [ 24 ]. ADAMTS1 and ADAM10 belong to the ADAM family and have both disintegrin and zinc metalloprotease domains, which implies that they might have functions related to the ECM and adhesion molecules by a similar approach [ 25 ]. Herein, we observed that overexpression and knockdown of ADAMTS1 respectively promoted and suppressed expression of L1-180 in HSC-3 and HSC-3M cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gene’s protein product has been suggested as a marker protein for neurodegeneration, 102 and hippocampal amyloid-β load was alleviated after introducing ADAMTS1 in a mouse model of AD. 103 Considering that five of six predicted AD-risk target genes were significantly differentially expressed in inhibitory neurons, it is plausible that altered glia-neuron communication affects inhibitory neurons more severely than excitatory neurons in the 12-month 3xTg-AD hippocampus. Four ligand-receptor pairs with AD risk genes also included an AD risk gene as a ligand ( Calm2 ) or receptor ( App ) of interactions originating from microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Both are involved in extracellular matrix damage and repair. 36 ADAMTS1 is thought to be involved in hydrolysis of APP and consequently decreases Aβ generation through inhibiting β-secretase-mediated cleavage. Clinically the gene may also affect cognitive ability by its effect on hippocampal amyloid processing.…”
Section: Discussionmentioning
confidence: 99%